2022
DOI: 10.3390/w14060972
|View full text |Cite
|
Sign up to set email alerts
|

Developing Predictive Equations for Water Capturing Performance and Sediment Release Efficiency for Coanda Intakes Using Artificial Intelligence Methods

Abstract: Estimation of withdrawal water and filtered sediment amounts are important to obtain maximum efficiency from an intake structure. The purpose of this study is to develop empirical equations to predict Water Capturing Performance (WCP) and Sediment Release Efficiency (SRE) for Coanda type intakes. These equations were developed using 216 sets of experimental data. Intakes were tested under six different slopes, six screens, and three water discharges. In SRE experiments, sediment concentration was kept constant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
0
0
Order By: Relevance
“…The results showed that the flow rate differences between simulations and experiments were smaller than 5%. In another research paper [20], 216 sets of experimental data were used to develop empirical equations to predict the water capture performance and sediment release efficiency for Coandă-type intakes using artificial intelligence methods. Initially, dimensionless parameters were created and subsequently analyzed by a multicollinearity analysis.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the flow rate differences between simulations and experiments were smaller than 5%. In another research paper [20], 216 sets of experimental data were used to develop empirical equations to predict the water capture performance and sediment release efficiency for Coandă-type intakes using artificial intelligence methods. Initially, dimensionless parameters were created and subsequently analyzed by a multicollinearity analysis.…”
Section: Introductionmentioning
confidence: 99%